In defense of a reflexive republican constitutional review. A comparative analysis of Tom Hickey and Richard Bellamy’s proposals (Perspectivas de las Ciencias Económicas y Jurídicas, 2023)
This paper focuses on the analysis of a complex and relevant political institution: constitutional review. Broadly speaking, its democratic legitimacy is evaluated from a normative philosophical perspective that matches with a contemporary republican approach. More precisely, it reconstructs the main representative republican concepts of Philip Pettit and comparatively analyzes the theoretical proposals of Richard Bellamy and Tom Hickey. Finally, four arguments are provided in defense of a possible alternative approach that commits the author to a reflexive republican conception and a system of multisituated constitutional review.
Keywords: constitutional review; democratic legitimacy; representative republicanism; reflexive republicanism; multi-situated design.